Perceptions of efficacy and safety of generic medicines in patients after percutaneous coronary intervention. (14th October 2021) - Pettersen, T; Schjott, J; Allore, H; Bendz, B; Borregaard, B; Fridlund, B; Larsen, A I; Nordrehaug, J E; Rotevatn, S; Wentzel-Larsen, T; Norekvaal, T M; ,
Abstract: Background: Generic medicines are bioequivalents to brand-name medicines, and compelling evidence for the safety and efficacy of generic medicines exists. However, negative perceptions about generic medicines can potentially reduce adherence to prescribed therapy and thereby efficacy of the treatment. Purpose: To describe patients' perceptions of generic medicines after percutaneous coronary intervention (PCI), and to investigate the association between perceptions and sociodemographic and clinical factors. Furthermore, we sought to investigate if these perceptions change over time. Methods: CONCARDPCI is a large-scale prospective multicentre cohort study on 3251 patients after PCI. The study was conducted between June 2017 and May 2020 at seven large referral PCI centres in Norway and Denmark. Clinical data, including invasive procedures and patient characteristics, were collected from the patients' medical records. Sociodemographic characteristics were obtained by self-report during index hospitalization after PCI. Postal or electronic questionnaires comprising questions regarding perceptions of generic medicines were distributed two (T1) and six (T2) months after discharge from hospital to included patients. The time intervals ensured that a sufficient amount of time had passed so that refill of prescriptions was necessary. To investigate perceptions of generic medicines and the associations with sociodemographic and clinical characteristics, logistic regression analysis was performed. Results: Most patients were men (78%), married or living with a partner (75%), elderly (mean age 66 years, SD11, range 20–96 years), and 28% were admitted to hospital due to non-ST-segment elevation myocardial infarction. At T1, 70% perceived generic medicines to be as effective, safe (68%), produce the same side effects (64%), and contain the same active ingredients as brand-name medicines (64%). Perceptions of generic medicines were similar at T2. No significant associations were found with age, marital status, living alone, taking ≥5 medications, or participation in cardiac rehabilitation. However, Danish patients (p<0.001), those with a higher education level (college/university≥4 years) (p=0.01), total household income >83, 000 Euro (p=0.007), female gender (p<0.001), and history of coronary artery disease (p=0.048) had more positive perceptions of generic medicines. Conclusion: Approximately one third of the patients had negative perceptions of generic medicines after PCI, and these negative perceptions do not seem to change substantially during the first six months after PCI. As negative perceptions of generic medicines have been found to be a barrier to medication adherence, improving patients' knowledge and confidence in generic medicines after PCI may be pivotal to reach treatment goals set forth by the 2018 ESC/EACTS Guidelines on myocardial revascularization. FUNDunding Acknowledgement: Type of funding sources: Other. Main funding source(s): The Western Norway Health Authority